A new sea star of the genus Leptasterias (Asteroidea: Asteriidae) from the Aleutian Islands - Clark, Roger N.; Jewett, Stephen C. (Zootaxa, 2015)
A new species of asteriid sea star of the genus Leptasterias (Order Forcipulatida) is described from the nearshore waters of the Aleutian Islands. Leptaterias tatei sp. nov. is distinguished from Leptasterias stolacantha Fisher, 1930, by the characteristics of the spines and pedicellariae. Geographic distribution is discussed and a key to the five-rayed Leptasterias of the Aleutian Islands is provided.